2016
DOI: 10.17221/39/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of fuel oil contaminated soils by activated persulfate in the presence of MnO<sub>2</sub>

Abstract: Mazloomi S., Nasseri S., Nabizadeh R., Yaghmaeian K., Alimohammadi K., Nazmara S., Mahvi A.H. (2016): Remediation of fuel oil contaminated soils by activated persulfate in the presence of MnO 2 . Soil & Water Res., 11: 131-138.In this study, batch system experiments were carried out for evaluating the capability of persulfate (PS) to remediate fuel oil contaminated soils. Remediation was performed by spiking soil samples with fuel oil and then treating the mixture with sodium PS. Different controlling factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Also another study declared that with increasing operation pressure removal of materials in water were increased [40, 41]. Other Researches of performance nanofiltration in Iran have done and revealed that NF membranes could decrease TDS in permeable very well if the concentration TDS in row water is around 3000 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Also another study declared that with increasing operation pressure removal of materials in water were increased [40, 41]. Other Researches of performance nanofiltration in Iran have done and revealed that NF membranes could decrease TDS in permeable very well if the concentration TDS in row water is around 3000 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions are caused by the radiation of photons resulting from UV radiation (7). However, with UV radiation in the presence of S 2 O 8 -2 , the photolysis process occurs which produces highly active SO 4radicals which have a high ability for oxidating organic compounds (12). Moreover, by increasing the concentration of S 2 O 8 -2 , an increase was observed in efficiency due to the increase in SO 4radical compared to the dye concentration, consistent with the results of Moradi et al (18).…”
Section: S2o8-2 Dosementioning
confidence: 99%
“…UV/ S 2 O 8 -2 is an AOP method with a significant expansion in environmental pollutant removal processes. The widespread use of S 2 O 8 in AOP processes may be its high oxidation ability (2.01 V), stability, low cost, easy storage, high solubility, and production of highly active radicals SO 4with the oxidation potential of 2.5 -3.1 V and OH • with the potential of 1.8 -2.8 (10)(11)(12). Equations 1 -3 show the pathways for the production of these radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The common approaches used for persulfate activation include thermal, ultraviolet (UV) irradiation, ultrasound (US), microwave (MW), magnetic nanoparticle‐functionalized carbon (MNP@C), TiO 2 ‐functionalized magnetic activated carbon (T@MPAC) and transition metal ion (e.g. Fe 2+ , Co 2+ , Mn 2+ , Ag 2+ and Ni 2+ ) methods . Among the transition metal ions, Fe 2+ is superior and is broadly employed for the decomposition of persulfate.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 2+ , Co 2+ , Mn 2+ , Ag 2+ and Ni 2+ ) methods. [25][26][27][28][29][30][31] Among the transition metal ions, Fe 2+ is superior and is broadly employed for the decomposition of persulfate. It is important to note that other metal ions are considered as toxic elements.…”
Section: Introductionmentioning
confidence: 99%